2020
DOI: 10.21203/rs.3.rs-36631/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic characterization of aggressive breast cancer cells exhibiting invasive phenotype: Impact of non-cytotoxic doses of 2-DG on diminishing invasiveness

Abstract: Abstract BackgroundMetabolic reprogramming is being recognized as a fundamental hallmark of cancer, and efforts to identify drugs that can target cancer metabolism are underway. In this study, we used human breast cancer (BC) cell lines and established their invading phenotype (INV) collected from transwell inserts to compare metabolome differences and evaluate prognostic significance of the metabolome in aggressive BC invasiveness.Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…For example, 1 mM 2-DG blocked cell viability and induced cytotoxicity in liver cancer cells HepG2 in this study. It has been reported that 1 mM 2-DG is toxic in breast cancer cell SUM149 [48], but it is not toxic in other breast cancer cells MDA-MB-231, HCC1937, HDQ-P1, and MCF-7 cells [48,49]. Thus, the findings from this study can be referenced in future studies.…”
Section: Metabolism Reprograming In Hepg2 Cellsmentioning
confidence: 53%
“…For example, 1 mM 2-DG blocked cell viability and induced cytotoxicity in liver cancer cells HepG2 in this study. It has been reported that 1 mM 2-DG is toxic in breast cancer cell SUM149 [48], but it is not toxic in other breast cancer cells MDA-MB-231, HCC1937, HDQ-P1, and MCF-7 cells [48,49]. Thus, the findings from this study can be referenced in future studies.…”
Section: Metabolism Reprograming In Hepg2 Cellsmentioning
confidence: 53%
“…GO of functions changed from cell adhesion and mRNA splicing and processing, to protein transport and vesicle-mediated transport, ephrin receptor signalling pathway, antigen processing, endocytosis in the later EV cargos. The pre-catastrophe EV cargo proteins reflect normal processes occurring in the BT-474 cells, for example cell-cell adhesion that would be evident in a minimally invasive cell-line [79]. The exact cause of the catastrophe is not evident from any of our data.…”
Section: Discussionmentioning
confidence: 77%
“…GO of functions changed from cell adhesion and mRNA splicing and processing, to protein transport and vesicleā€mediated transport, ephrin receptor signalling pathway, antigen processing, endocytosis in the later EV cargos. The preā€catastrophe EV cargo proteins reflect normal processes occurring in the BTā€474 cells, for example cellā€cell adhesion that would be evident in a minimally invasive cellā€line (Fujita et al., 2020). The exact cause of the catastrophe is not evident from any of our data, for example we do not see a change in the cellular localisation of the EV proteins that could indicate cell lysis.…”
Section: Discussionmentioning
confidence: 99%